The treatment of singularities associated with a dislocation segment with applications. (4th February 2022) - Siddique, Abu Bakar; Khraishi, Tariq A.
Quantification of the stress field around dislocations is important in dislocation theory and can have profound effect on computations involving dislocations such as in discrete dislocation dynamics (DDD) simulations. In this paper, the original work by Devincre (1995) on the stress field of a linear dislocation segment is carefully studied and based on three regions of space, a physics-based algorithm is presented to treat any singularity, weak or strong, associated with the self-stress of the segment. The paper shows several utilisations of this method. Two of these utilisations concern the 'collocation-point' method for capturing free-surface effects on dislocation forces and movement. In one, an on-the-fly mesh was utilised, and in the other an unstructured mesh was utilised. Results were validated where appropriate and both static and dynamic implementations are presented.